3D Ni-Co sulfoxide nanosheet arrays electrodeposited on Ni foam: A bifunctional electrocatalyst towards efficient and stable water splitting. (1st December 2018) - Li, Changqing; Zhao, Xu; Liu, Yiwen; Wei, Wei; Lin, Yuqing
Abstract: Developing highly active and stable electrocatalysts from earth-abundant elements are imperative for the large-scalable production of hydrogen. Herein, the three dimensional amorphous NiCoSx Oy nanosheets arrays directly grow on Ni foam (NiCoSx Oy NSs/NF) through a facile one-step electrodeposition is firstly reported. The special in-situ grown 3D nanosheets arrays, largely exposed active sites and enhanced electrical conductivity enable the resultant NiCoS0.14 O3.25 NSs/NF to possess remarkable electrocatalytic performance and stability towards water splitting in 1 M KOH. Specifically, the introduction of S ligand into the hydroxides through a straightforward and convenient electrodeposition method boost the robust composition and comprehensive activity of the NiCoSx Oy NSs. Such binder-free, easily prepared NiCoS0.14 O3.25 NSs/NF electrode requires the overpotential of 250 mV and 170 mV at 10 mA cm −2 for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), respectively. When functionalizing as two identical cathode and anode in an alkaline electrolyzer, NiCoS0.14 O3.25 NSs/NF displays the efficient and robust property on both OER and HER. Remarkably, serving as bifunctional electrode in alkaline electrolyzer, it only needs 1.64 V to reach the current density of 20 mA cm −2 . This study provides a valuable guideline to synthesize non-noble and efficient bifunctional electrocatalysts using a time-saving but facile electrochemical method. Graphical abstract: